Switchable erbium-doped fiber laser (EDFL) using non-adiabatic microfiber - Salim, Muhammad Aizi Mat; Ali, Norazida; Azzuhri, Saaidal Razalli; Abdul Khudus, Muhammad Imran Mustafa; Jamaludin, Jafferi; Faruki, Md Jahid; Amiri, Iraj Sadegh (Elsevier, 2019)
We have investigated the operation principle of the switchable EDFL which stands for the erbium-doped fiber laser, where a non-adiabatic microfiber has been fabricated and used. Utilizing the flame-brushing technique, the optical microfiber has been fabricated and afterward, it has been inserted into the EDFL cavity, therefore by proposing the setup configuration, the single and multi-wavelength laser could be generated. By applying the different filtering effects of the microfiber, the results of a single wavelength laser (one set), dual-wavelength laser (three sets) and triple wavelength laser (two sets) could be generated over a wavelength range of 1560–1565 nm. The signal to noise ratio (SNR) of 42–50 dB is obtained from the experiment with acceptable wavelength and power fluctuation over the test period of 30 min. Proposed switchable EDFL shows tunable and stable single and multi-wavelength laser generation in C band region. © 2019 Elsevier Inc.